Prevalence of extended-spectrum beta-lactamase-positive Klebsiella pneumoniae isolates in the Czech Republic - Kolar, M; Latal, T; Cermak, P; Bartonikova, N; Chmelarova, E; Sauer, P; Kesselova, M (International journal of antimicrobial agents, 2006)
This study focused on the prevalence and molecular biology of extended-spectrum beta-lactamase (ESBL)-positive Klebsiella pneumoniae isolates collected in the Czech Republic. Clinical material from patients hospitalised in 16 Czech hospitals in September 2004 was used to isolate K. pneumoniae strains. Strains were identified by standard identification procedures. Susceptibility of the strains to antibiotics was tested using a microdilution method. The double-disk synergy test and combination disk method were used to determine ESBL production. Molecular biology characteristics of ESBL-positive isolates were determined using genomic DNA isolation, XbaI restriction digestion and pulsed-field gel electrophoresis differentiation. The acquired restriction maps of individual isolates were compared using GelCompar II software and their relationships were determined. During the 3-week period, 483 K. pneumoniae strains causing clinically detectable diseases were isolated. Of these, 117 (24.2%) were determined to be ESBL-positive. The prevalence of ESBL-positive isolates was 38.9% in Intensive Care Units (ICUs) and 13.1% in standard wards. More than 50% of ESBL-positive isolates were treated effectively only with meropenem (98%), cefoperazone/sulbactam (61%) and amikacin (54%). Conversely, ESBL-negative isolates showed high susceptibility to all tested antibiotics (76-99%). Molecular biology analysis identified 18 clonal types containing two to six identical isolates. Seventeen clones usually contained isolates from only one hospital; isolates from two hospitals were identified only in one clone. Based on the abovementioned results, the prevalence of ESBL-positive K. pneumoniae isolates in the Czech Republic can be perceived as relatively high, especially in ICUs. Extensive spread of 'epidemic clones' within Czech hospitals and, to a limited extent, between them can be demonstrated.
Keywords: beta-Lactamases; beta-laktamasy; Klebsiella pneumoniae; Drug Resistance, Microbial; Česká republika; antibiotická rezistence; Czech Republic